The handbook of spiritual development in childhood and adolescence - Roehlkepartain, Eugene C., 1962-; Sage Publications, inc.; Sage eReference (Online service) (Thousand Oaks, Calif. : SAGE Publications, 2006)
Drawing together the work of leading scholars focused on spiritual development in childhood and adolescence, this volume demonstrates that spiritual development. It represents diverse traditions and approaches from multiple disciplines such as psychology, human development and family studies, sociology, and religious studies.
Spiritual development in childhood and adolescence : moving to the scientific mainstream / Eugene C. Roehlkepartain ... [et al.] -- Foundations for the scientific study of spiritual development in childhood and adolescence. Toward a developmental analysis of religious and spiritual development / W. George Scarlett ; Stages of faith from infancy through adolescence : reflections on three decades of faith development theory / James W. Fowler and Mary Lynn Dell ; Spiritual development : intersections and divergence with religious development / David Hay, K. Helmut Reich, and Michael Utsch ; On making humans human : spirituality and the promotion of positive youth development / Richard M. Lerner ... [et al.] ; Philosophical issues in spiritual education and development / Hanan A. Alexander and David Carr ; Measurement and research design in studying spiritual development / Richard L. Gorsuch and Donald Walker -- Descriptive approaches to spiritual development. The demographics of spirituality among youth : international perspectives / Laura H. Lippman and Julie Dombrowski Keith ; The changing global context of adolescent spirituality / Suman Verma and Madelene Sta. Maria ; Spiritual and religious pathology in childhood and adolescence / Linda M. Wagener and H. Newton Malony ; Non-Western approaches to spiritual development among infants and young children : a case study from West Africa / Alma Gottlieb ; Spiritual experiences and capacities of children and youth / Tobin Hart -- Spirituality and human development : exploring connections. A neuropsychological perspective on spiritual development / Andrew B. Newberg and Stephanie K. Newberg ; Attachment and spiritual development in childhood and adolescence / Pehr Granqvist and Jane R. Dickie ; Cognitive-cultural foundations of spiritual development / Carl N. Johnson and Chris J. Boyatzis ; The relationship between moral and spiritual development / Lawrence J. Walker and Kevin S. Reimer ; The relationship between spiritual development and civic development / Thomas M. Donnelly ... [et al.] ; The relation between spiritual development and identity processes / Janice L. Templeton and Jacquelynne S. Eccles ; Personality and spiritual development / Teresa T. Kneezel and Robert A. Emmons -- The ecologies of spiritual development. Ethnicity, culture, and spiritual development / Jacqueline S. Mattis ... [et al.] ; The family as a context for religious and spiritual development in children and youth / Chris J. Boyatzis, David C. Dollahite, and Loren D. Marks ; Mentors, friends, and gurus : peer and nonparent influences on spiritual development / Kelly Dean Schwartz, William M. Bukowski, and Wayne T. Aoki ; Congregations : unexamined crucibles for spiritual development / Eugene C. Roehlkepartain and Eboo Patel -- Developmental outcomes of spiritual development. Religious coping by children and adolescents : unexplored territory in the realm of spiritual development / Annette Mahoney, Sara Pendleton, and Heidi Ihrke ; Resilience and spirituality in youth / Emily Crawford, Margaret O'Dougherty Wright, and Ann S. Masten ; Delinquency : a quest for moral and spiritual integrity? / Ronnie Frankel Blakeney and Charles David Blakeney ; Spiritual development and adolescent well-being and thriving / Pamela Ebstyne King and Peter L. Benson ; Religion, spirituality, and children's physical health / Doug Oman and Carl E. Thoresen -- Toward the future in practice, policy, and research. Spiritually oriented psychotherapy with youth : a child-centered approach / Lisa Miller and Brien Kelley ; Bridging the gap : from social science to congregations, researchers to practitioners / Dean Borgman ; Integrating spiritual development into child and youth care programs and institutions / Daniel G. Scott and Douglas Magnuson ; Bridging to public policy and civil society / Steve Hornberger, Roberta Furtick Jones, and Robert L. Miller Jr. ; Childhood spirituality : strengthening the research foundation / Donald Ratcliff and Rebecca Nye ; The science of child and adolescent spiritual development : definitional, theoretical, and field-building challenges / Peter L. Benson.
Includes bibliographical references (p. 494-497) and indexes.
Description based on print version record.
Keywords: Youth -- Religious life -- Handbooks, manuals, etc; Faith development -- Handbooks, manuals, etc; Youth -- Psychology -- Handbooks, manuals, etc; Spirituality -- Handbooks; Child Development -- Handbooks; Adolescent Development -- Handbooks; Jeunesse -- Vie religieuse -- Guides, manuels, etc; Foi -- Développement -- Guides, manuels, etc; RELIGION / Religious Intolerance, Persecution & Conflict; Electronic books